Evaluation of service-oriented architecture adoption maturity model for sustainable development - Hamzah, Mohd Hamdi Irwan; Baharom, Fauziah; Mohd, Haslina; Omar, Mohd Hasbullah (Universiti Teknikal Malaysia Melaka, 2018)
Goal-oriented evaluation is a fundamental approach to monitor and ensure that all measurement activities are being carried out in the context of a well-defined evaluation goal. However, this study found that the previous ServiceOriented Architecture maturity models have not comprehensively considered providing an appropriate method for evaluating the Service-Oriented Architecture adoption. Therefore, this study aims to provide an evaluation method for Service-Oriented Architecture adoption by using goal-oriented approach. The reason is that in order for the evaluation to be effective, it must be driven by a goal. Thus, this study adapts the goal-oriented approach in order to provide an effective evaluation method for evaluating the Service-Oriented Architecture adoption. This study also extends the metric component in Goal-Question-Metric by providing a scale for each metric based on the NPLF rating scale adapted from ISO/IEC 15504. Conclusively, this paper has shown that goaloriented approach can be used to evaluate the Service-Oriented Architecture adoption through Goal-Question-Metric. GoalQuestion-Metric also provides a hierarchical structure that can be refined in order to evaluate the SOA adoption towards a sustainable development effectively. Sustainable development means that the teams work at consistence and continuous speed to produce a quality result. Therefore, the proposed model may benefit the Service-Oriented Architecture practitioner and quality editor in software engineering domain.